1982
DOI: 10.1177/01454455820061005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Fast and Slow Models on Drinking Rate

Abstract: Two male subjects and one female subject drank beer with same sex confederate models in a simulated bar. An ABACA reversal design was used. Condition A indicated subject baseline drinking rate. Condition B consisted of one confederate modeling a high rate concurrent with a second confederate modeling a low rate. For Condition C, confederates modeled in the opposite direction to Condition B. Sessions were of one hour duration. Each condition was continued until stability was reached. Subjects consistently match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Thus, although educational and prevention programs that provide light drinking models may be generally useful for young male social drinkers, they may be particularly effective for those with a family history of problem drinking. The feasibility of such prevention training has already been indicated byDeRicco and Niemann (1982), who demonstrated that a subject's characteristic intake of alcohol could be dramatically reduced by confederate models who lowered their drinking below that of the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although educational and prevention programs that provide light drinking models may be generally useful for young male social drinkers, they may be particularly effective for those with a family history of problem drinking. The feasibility of such prevention training has already been indicated byDeRicco and Niemann (1982), who demonstrated that a subject's characteristic intake of alcohol could be dramatically reduced by confederate models who lowered their drinking below that of the subject.…”
Section: Discussionmentioning
confidence: 99%